Constitutional Review as a Democratic Instrument - Kriszta Kovács; Gábor Attila Tóth (Review of Central and East European Law, 2023)
The article situates Rosalind Dixon's Responsive Judicial Review in constitutional legal literature and engages with its central message by introducing the idea of constitutional courts as accessible democratic institutions. It compares constitutional review in a well-functioning and a declining democracy. After considering the relationship between democratic self-government and constitutional review, the article argues that a lawfully established, accessible, yet reasonably self-restraining constitutional court with the power of procedural and substantive review can be understood as a democratic institution. To support this claim, the article offers the example of Hungary, where democratization coincided with the birth of accessible constitutional review and where the decay of democracy has been accompanied by the decline of constitutional review. It concludes that constitutional justices can always have a choice. They can contribute to an autocratic transformation or resist the autocratic government by performing a Herculean task.
Keywords: 340; Constitutional review; democracy; access to justice; actio popularis; Hungarian Constitutional Court